Change of Skin Blood Flow at Lower Limb under External Pressure (Journal of Fiber Bioengineering and Informatics, 2008)
It has been reported that external pressure exerted on lower limbs helps to accelerate bloodflow during doing exercise or playing sports and thus improving sports performance. In this paper, thepressure effect on skin blood flow was investigated. Pressures of various magnitudes were exerted onankles and calves respectively by using a sphygmomanometer, under which the skin blood flow changewas observed. The results showed that the skin blood flow increased when pressure of certain levelwas loaded at ankle or calf; however, as the pressure magnitude exceeding certain value, it turned todecrease. Moreover, ankles seemed to bear much higher pressure than calves. The mechanism of skinblood flow responding to external pressure was also discussed.
Keywords: external pressure; skin blood flow; lower limb